ENERGY-EFFICIENT LIGHTING CONTROL SYSTEM BASED ON MQTT AND RASPBERRY PI - Ubale, Ranjana; Khandge, Yogita; Kulkarni, Nitin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Energy consumption in lighting systems significantly contributes to electricity usage, especially in commercial and industrial environments. As demand for energy efficiency grows, intelligent lighting control systems offer a practical solution to optimize energy consumption. This research proposes designing and implementing an energy-efficient lighting control system based on the MQTT (Message Queuing Telemetry Transport) protocol and the Raspberry Pi platform. The goal is to develop an energy-efficient lighting solution that reduces energy waste, improves user comfort, and provides real-time data for better energy management in residential and industrial buildings. The MQTT protocol enables communication between the Raspberry Pi and other devices in the system, such as sensors and light bulbs. By using MQTT brokers, the system is capable of exchanging messages in real time, triggering light adjustments based on sensor data. The system supports remote control capabilities through a smartphone or computer, allowing users to modify the lighting settings from any location, thus offering enhanced flexibility and ease of use. The MQTT protocol publish-subscribe model enables multiple devices to interact with minimal latency, ensuring fast and efficient control of the lighting system. To ensure energy efficiency, the system continuously monitors energy consumption by tracking the power usage of connected light bulbs. It records the data on the Raspberry Pi and provides real-time feedback to the user via an online interface or mobile app. The energy consumption data is displayed in graphical formats, allowing users to analyze trends and make informed decisions about lighting usage. Furthermore, the system offers the potential for machine learning algorithms to optimize energy consumption patterns based on historical data, allowing the system to “learn” and predict energy-saving strategies for future use. The design of the system is modular and scalable, making it adaptable to a wide range of applications. Whether in a single room or a large industrial complex, the system can be expanded to accommodate additional sensors, lights, and control units. The system can be customized to meet specific energy-saving goals or to integrate with existing smart home systems, providing a flexible solution that can evolve as user needs change over time. In conclusion, this project demonstrates the potential of combining the Raspberry Pi platform and MQTT communication protocol to create a smart, energy-efficient lighting control system. By integrating real-time sensor data with automated lighting adjustments and remote-control features, the system not only improves user comfort but also contributes to significant energy savings. The scalability, flexibility, and modular nature of the design make it a promising solution for a variety of applications, from residential to industrial settings, promoting sustainability and reducing the environmental impact of lighting systems.